Ethanolic Extract of Moringa oleifera L. Increases Sensitivity of WiDr Colon Cancer Cell Line Towards 5-Fluorouracil - Nur, Kholid Alfan; Putri, Herwandhani; Cahyani, Fany Mutia; Katarina, Aulia; Susidarti, Ratna Asmah; Meiyanto, Edy (Indonesian Journal of Cancer Chemoprevention, 2010)
For more than four decades, combination chemotherapy (co-chemotherapy) has been employed as a means to increase the effectiveness of chemotherapy regiments. The aim of our research is to investigate the activity ofÃÂ  Moringa oleiferaÃÂ  L. (tanaman kelor) ethanolic extract (MEE) as a co-chemotherapy agent with 5-fluorouracil (5-FU) on WiDr colon cancer cell line. Evaluation of MEE potency as a co-chemotherapy agent with 5-FU was based on cytotoxic activity based on percent cell viability via MTTÃÂ  assay, and based on apoptosis observation via the double staining method using acrydin orange Ã¢â¬â ethidium bromide (AE) as the staining reagent.Cytotoxicity evaluation of single treatment using concentrations of 5, 20, 50, 100,125, and 250 ÃÂµg/ml of MEE reduced cell viability 24 hours post-treatment. 5, 50, and 250 ÃÂµg/ml of MEE was chosen as the combination concentrations with 1000 ÃÂµM 5-FU. MTT assay 24 hours and 48 hours post-combination treatment showed significant cell viability reduction in comparison to those of single treatments. Apoptosis observation using the double staining method shows the presence of apoptotic cells 48 hours post combination treatment. MEE is a potential co-chemotherapy agentÃÂ  by increasing the sensitivityÃÂ  of WiDr colon cancer cell line towards 5-FU.